2006
DOI: 10.1111/j.1744-7909.2006.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen and Resource Limitation in Veratrum nigrum L. (Liliaceae), an Andromonoecious Herb

Abstract: Pollen limitation and resource limitation were invoked to account for the pattern that flowering plants produce more flowers and ovules than fruits and seeds. This study aimed to determine their relative importance in Veratrum nigrum, a self-compatible, perennial, andromonoecious herb. In order to determine whether female production was limited by pollen grains on stigmas or by available resources, we performed supplemental hand pollination in three populations, male-flower-bud removal in three other populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…Fruiting success probably was limited by resources and not by the number of fertile ovaries. The hand pollination experiment showed that seed production also was not limited by pollen, although this may vary among sites and among years depending mainly on insect pollinator abundance (Liao et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fruiting success probably was limited by resources and not by the number of fertile ovaries. The hand pollination experiment showed that seed production also was not limited by pollen, although this may vary among sites and among years depending mainly on insect pollinator abundance (Liao et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…If so, seed set in small plants should be limited by compatible pollen gains deposited on stigma, rather than by resources available for seed maturation. However, this hypothesis is unlikely since the female reproductive success is not pollen‐limited, but resource‐limited in V. nigrum (Liao et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, the occurrence of femalesterile systems has been highlighted in an increasing number of studies dealing with taxa in the order Liliales (e.g., Beisenova et al, 2015;Dafni & Shmida, 2002;Liao, Song, & Zhang, 2006;Liao & Zhang, 2008;Nishikawa, 1998;Schnittler et al, 2017;Wang, Zhai, & Zhang, 2018). In particular, within Liliaceae, several cases have been previously reported in Fritillaria (Mancuso & Peruzzi, 2010;Matsuura, 1934;Peruzzi, 2012;Peruzzi, Mancuso, & Gargano, 2012;Shimizu et al, 1998), Gagea (including Lloydia) (Jones & Gliddon, 1999;Niu, Gong, Peng, Sun, & Li, 2017) and Lilium (Peruzzi, 2012;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%